Yoga module for somatoform pain disorders: Development, content validation, and feasibility testing - Jha, Monika; Dumbala, Sowjanya; Gulati, Kankan; Bhargav, Hemant; Arasappa, Rashmi; Varambally, Shivarama; Gangadhar, B; Desai, Geetha (International journal of yoga, 2021)
Background: Yoga practices have been found to be useful in chronic pain conditions but studies focussing specifically on somatoform pain disorders (SPDs) are limited. Aims: Current study aims to develop and test the feasibility of a yoga program for patients with SPDs. Materials and Methodology: Athorough search of traditional and contemporary literature was performed with the objective of formulating a yoga program for reducing chronic non-specific pain and associated psychological distress. Content validity of the program was then determined by taking the opinion of 18 yoga experts (who had >5 years of experience in treating mental health disorders) using content validation ratio (CVR) through Lawshe's formula. The feasibility of the module was tested on 10 subjects diagnosed with SPDs as per the International Classification of Diseases (ICD) -10 criteria using standard scales. Results: In the finalized module, 70.83% (34 out of 48 items) of the practices were retained along with the modifications as suggested by the experts. Two practices were not found to be feasible (Trikonasana and Shalabhasana) and hence were removed from the final module. A significant reduction in pain severity was observed in the subjects after practising the yoga module for 2 weeks. The content validity index for the whole module (average of all CVRs) was 0.55. Conclusions: Ayoga module was developed for SPD. The content validity of the module was found to be good. The module was found safe and potentially useful for reducing pain severity in patients with SPD. Future studies should test the efficacy of the developed program through a randomized controlled clinical trial.